Method for producing polyvinyl alcohol fiber containing ferroelectric substance and fiber made of ferroelectric substance

JP7651295B2Active Publication Date: 2025-03-26KURARAY CO LTD +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2020210509
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-18
Publication Date
2025-03-26
Estimated Expiration
2040-12-18

Smart Images

  • Figure 0007651295000001
    Figure 0007651295000001
Patent Text Reader

Abstract

To provide a polyvinyl alcohol fiber containing ferroelectric particles having high toughness and excellent flexibility and handleability.SOLUTION: A method for producing a polyvinyl alcohol fiber comprises: adding, to an organic solvent, a polyvinyl alcohol fiber containing a ferroelectric material and a polyvinyl alcohol having an average degree of polymerization of 2000 or more, a fiber structure ferroelectric material containing the polyvinyl alcohol fiber at least in part, and a polyvinyl alcohol having a degree of polymerization of 2000 or more to give a spinning stock solution; and discharging the spinning stock solution to a solidifying liquid having a solidifying ability for the polyvinyl alcohol polymer.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to polyvinyl alcohol fibers that are suitably used for producing fibers made of ferroelectrics, a fiber structure containing the fibers, a method for producing the fibers, and a method for producing fibers made of ferroelectrics using the fibers. [Background technology]

[0002] In recent years, there has been a demand for electronic devices to be smaller, more complex, thinner, and more powerful, and this has created a demand for dielectric materials that have excellent dielectric constants and are easy to process into various shapes. Among dielectric materials, metal titanates have a high dielectric constant, and due to their excellent dielectric properties, they are widely used as dielectric materials for ceramic multilayer capacitors and other devices. Metal titanates are also used as modifiers for polymers and rubbers, and by adding them to polymeric materials, composites with high dielectric constants can be obtained.

[0003] However, in such composite materials, it is necessary to highly fill the ferroelectric to realize the dielectric properties, but the highly filled ferroelectric may cause loss of moldability and flexibility. If the moldability and flexibility are lost, it may be difficult to completely remove voids during the molding process or to obtain the desired shape of the molded product.

[0004] In addition, it is difficult to process the ferroelectric material into a fiber shape, particularly into a thin continuous fiber shape, which is subjected to a certain tension during the manufacturing process, and therefore a fibrous material containing a ferroelectric material that has both sufficient performance and ease of handling is desired. If a fibrous material that has both such performance and ease of handling could be provided, it would be possible to process the material into various forms depending on the application, such as dielectric materials with complex shapes, and it could be used as a new electronic material.

[0005] As a fibrous material, for example, Patent Document 1 discloses an organic fibrous composition in which composite metal titanate fibers are oriented in the fiber axis direction and dispersed in an organic polymer. Forming a ferroelectric material into a fiber shape is disclosed in, for example, Patent Documents 2 and 3.

[0006] Patent document 2 discloses a method for producing fibrous barium titanate, which comprises adsorbing titanium ions and barium ions onto an alginate gel formed into a continuous fiber shape, drying the alginate gel while stretching it in the longitudinal direction of the fiber, and then calcining the alginate gel in air. Patent Document 3 discloses a long fibrous alkali titanate having a high flexibility and consisting of a polycrystalline structure continuously aligned in one direction. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Japanese Patent Application Publication No. 09-241918 [Patent Document 2] Japanese Patent Application Publication No. 4-272228 [Patent Document 3] Japanese Patent Application Publication No. 4-202015

[0008] However, the organic fibrous compositions described in Patent Documents 1 and 2 both have a large fiber diameter, and the fibers obtained are difficult to wind or process, and are considered to have poor handleability. Patent Document 3 discloses a fiber with a small fiber diameter, but the shape of the fiber is considered to be whisker-like, not fibrous.

[0009] Therefore, the fibers containing a ferroelectric material or the fibers made of a ferroelectric material known so far are insufficient in terms of fiber diameter and flexibility, and further improvements are desired. Summary of the Invention [Problem to be solved by the invention]

[0010] Therefore, the present invention aims to provide a polyvinyl alcohol fiber containing a ferroelectric substance that has high toughness and excellent flexibility and handleability. Another object of the present invention is to provide a method for producing a polyvinyl alcohol fiber containing a ferroelectric substance that has high toughness and excellent flexibility and handleability, and a fiber structure having the fiber. Another object of the present invention is to provide a method for producing a fiber made of a ferroelectric substance using a polyvinyl alcohol fiber containing a ferroelectric substance. [Means for solving the problem]

[0011] The inventors noticed that a fibrous dielectric material is obtained by firing fibers containing a ferroelectric and polyvinyl alcohol, and completed the present invention based on the fact that polyvinyl alcohol fibers containing a ferroelectric can serve as a precursor for fibers made of a ferroelectric.

[0012] That is, the present invention provides [1] a polyvinyl alcohol fiber containing a ferroelectric material and polyvinyl alcohol having an average degree of polymerization of 2000 or more; [2] The polyvinyl alcohol fiber according to [1] above, having a fiber diameter of 100 μm or less; [3] The polyvinyl alcohol fiber according to [1] or [2], wherein the ferroelectric substance is present in an amount of 20 to 1900 parts by mass per 100 parts by mass of the polyvinyl alcohol. [4] The polyvinyl alcohol fiber according to any one of [1] to [3], wherein the ferroelectric has a relative dielectric constant of 300 or more. [5] The polyvinyl alcohol fiber according to any one of [1] to [4], wherein the ferroelectric material contains at least a metal titanate. [6] The polyvinyl alcohol fiber according to the above [5], wherein the metal of the metal titanate is an alkali metal or an alkaline earth metal. Regarding. Furthermore, the present invention [7] A fiber structure comprising at least a part of the polyvinyl alcohol fiber according to any one of [1] to [6] above. [8] The method for producing polyvinyl alcohol fiber according to any one of [1] to [6], further comprising adding a ferroelectric material and polyvinyl alcohol having a degree of polymerization of 2000 or more to an organic solvent to prepare a spinning dope, and discharging the spinning dope into a solidifying liquid having a solidifying ability for the polyvinyl alcohol polymer; [9] A method for producing a fiber made of a ferroelectric material, comprising calcining the polyvinyl alcohol fiber according to any one of [1] to [6] above at 1200 to 1400°C; Regarding. Effect of the Invention

[0013] According to the present invention, a polyvinyl alcohol fiber containing a ferroelectric material, which has high toughness and excellent flexibility and handleability, is provided. Also, according to the present invention, a method for producing a polyvinyl alcohol fiber containing a ferroelectric material, which has high toughness and excellent flexibility and handleability, and a fiber structure having the fiber are provided. Furthermore, the present invention provides a method for producing a fiber made of a ferroelectric material using a polyvinyl alcohol fiber containing a ferroelectric material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The present invention will be specifically described below.

[0015] The polyvinyl alcohol fiber of the present invention contains a ferroelectric material and polyvinyl alcohol having an average degree of polymerization of 2000 or more, and can be converted into a fiber made of a ferroelectric material by baking as described below.

[0016] A ferroelectric is a material that retains spontaneous polarization even after the applied voltage is removed. This material has the property that the direction of the spontaneous polarization inside the material can be changed arbitrarily by changing the direction of the applied external electric field. The relative dielectric constant of a ferroelectric is usually 50 or more, and from the viewpoint of utilizing ferroelectricity, it is preferably 100 or more, more preferably 300 or more, and particularly preferably 1000 or more.

[0017] Examples of ferroelectrics include metal titanates, lead zirconate titanates, potassium dihydrogen phosphate, potassium arsenate, aluminum guanidine sulfate, Rochelle salts, sodium nitrite, ammonium sulfate, ammonium cadmium sulfate, glycine sulfate, calcium borate hydrate, etc. Among these, metal titanates and Rochelle salts are preferred. The metal of the metal titanates is more preferably an alkali metal or an alkaline earth metal, and specific examples include barium titanate, potassium titanate, and strontium titanate. The above ferroelectrics may be used alone or in combination of two or more.

[0018] The polyvinyl alcohol fiber of the present invention contains the above-mentioned ferroelectric material and polyvinyl alcohol having an average degree of polymerization of 2000 or more. The polyvinyl alcohol used in the present invention is a saponified vinyl ester polymer obtained by polymerizing vinyl ester monomers. Examples of the vinyl ester monomer include vinyl formate, vinyl acetate, vinyl propionate, vinyl valerate, vinyl laurate, vinyl stearate, vinyl benzoate, vinyl pivalate, and vinyl versatate, and among these, vinyl acetate is preferred.

[0019] The vinyl ester polymer is preferably one obtained by using one or more vinyl ester monomers as a monomer, more preferably one obtained by using one vinyl ester monomer as a monomer, and may be a copolymer of one or more vinyl ester monomers and another monomer copolymerizable therewith.

[0020] Examples of other monomers copolymerizable with vinyl ester monomers include ethylene; olefins having 3 to 30 carbon atoms, such as propylene, 1-butene, and isobutene; acrylic acid or a salt thereof; acrylic acid esters, such as methyl acrylate, ethyl acrylate, n-propyl acrylate, i-propyl acrylate, n-butyl acrylate, i-butyl acrylate, t-butyl acrylate, 2-ethylhexyl acrylate, dodecyl acrylate, and octadecyl acrylate; methacrylic acid or a salt thereof; methyl methacrylate, ethyl methacrylate, methacrylic acid, and the like. Methacrylic acid esters such as n-propyl methacrylate, i-propyl methacrylate, n-butyl methacrylate, i-butyl methacrylate, t-butyl methacrylate, 2-ethylhexyl methacrylate, dodecyl methacrylate, and octadecyl methacrylate; acrylamide, N-methylacrylamide, N-ethylacrylamide, N,N-dimethylacrylamide, diacetone acrylamide, acrylamidopropanesulfonic acid or a salt thereof, acrylamidopropyldimethylamine or a salt thereof, N-methylolacrylamide or a derivative thereof, etc. methacrylamide derivatives such as methacrylamide, N-methylmethacrylamide, N-ethylmethacrylamide, methacrylamidepropanesulfonic acid or a salt thereof, methacrylamidepropyldimethylamine or a salt thereof, N-methylolmethacrylamide or a derivative thereof; N-vinylamides such as N-vinylformamide, N-vinylacetamide, N-vinylpyrrolidone; vinyl ethers such as methyl vinyl ether, ethyl vinyl ether, n-propyl vinyl ether, i-propyl vinyl ether, n-butyl vinyl ether, i-butyl vinyl ether, t-butyl vinyl ether, dodecyl vinyl ether, stearyl vinyl ether; vinyl cyanides such as acrylonitrile and methacrylonitrile; vinyl halides such as vinyl chloride, vinylidene chloride, vinyl fluoride, and vinylidene fluoride; allyl compounds such as allyl acetate and allyl chloride; maleic acid or a salt, ester, or acid anhydride thereof; itaconic acid or a salt, ester, or acid anhydride thereof; vinyl silyl compounds such as vinyltrimethoxysilane; and isopropenyl acetate.The vinyl ester polymers described above can have structural units derived from one or more of these other monomers.

[0021] From the viewpoint of the strength of the obtained fiber, the proportion of the structural units derived from the other monomers in the vinyl ester polymer is preferably 15 mol % or less, more preferably 5 mol % or less, based on the number of moles of all structural units constituting the vinyl ester polymer. The content of the other monomers may be 0, but when the vinyl ester polymer contains the other monomers, the proportion of the structural units derived from the other monomers is preferably 0.02 mol % or more, more preferably 0.1 mol % or more, based on the number of moles of all structural units constituting the vinyl ester polymer.

[0022] The polyvinyl alcohol used in the polyvinyl alcohol fiber of the present invention can be obtained by saponifying the vinyl ester polymer described above. The polyvinyl alcohol used in the polyvinyl alcohol fiber of the present invention may be a polyvinyl alcohol having at least one functional group selected from the group consisting of a sulfonic acid group, a sulfonate group, a maleic acid group, an itaconic acid group, an acrylic acid group, and a methacrylic acid group.

[0023] The average degree of polymerization (viscosity average degree of polymerization) of the polyvinyl alcohol is not less than 2000. From the viewpoint of handleability when made into a fiber containing a ferroelectric substance, it is preferably not less than 2200, more preferably not less than 2400. From the viewpoint of spinnability of the fiber containing a ferroelectric substance, the degree of polymerization is preferably not more than 20000, more preferably not more than 10000.

[0024] The average degree of polymerization (Pо) is measured in accordance with JIS K 6726-1994, and is calculated from the intrinsic viscosity [η] (unit: deciliter / g) measured in water at 30°C after resaponifying and purifying polyvinyl alcohol, using the following formula: Po = ([η]×10 4 / 8.29) (1 / 0.62)

[0025] From the viewpoint of the strength of the resulting polyvinyl alcohol fiber, the saponification degree of the polyvinyl alcohol is preferably 98 mol % or more, and more preferably 99 mol % or more. The saponification degree is measured in accordance with JIS K 6726.

[0026] From the viewpoint of the electrical properties and handling of the resulting fiber made of a ferroelectric, the polyvinyl alcohol fiber of the present invention preferably contains the ferroelectric in an amount of 20 to 1900 parts by mass per 100 parts by mass of the polyvinyl alcohol, more preferably 100 parts by mass or more, and even more preferably 400 parts by mass or more, from the viewpoint of the electrical properties of the fiber made of a ferroelectric. From the viewpoint of handling of the fibers containing a ferroelectric substance, the amount is more preferably 1600 parts by mass or less, and even more preferably 1200 parts by mass or less.

[0027] The polyvinyl alcohol fiber of the present invention may contain a resin other than polyvinyl alcohol or an inorganic substance other than a ferroelectric substance within a range that does not impair the effects of the present invention. In addition, various additives such as a plasticizer, a crosslinking agent, an antioxidant, a stabilizer, a lubricant, a processing aid, an antistatic agent, a colorant, an impact resistance aid, and a foaming agent may be blended as necessary.

[0028] When the polyvinyl alcohol fiber of the present invention contains a resin other than polyvinyl alcohol or an inorganic substance other than a ferroelectric substance, the content thereof is preferably 20 parts by mass or less based on 100 parts by mass of the polyvinyl alcohol.

[0029] The fiber diameter of the polyvinyl alcohol fiber of the present invention is preferably 100 μm or less from the viewpoint of handling, more preferably 90 μm or less, and even more preferably 50 μm or less from the viewpoint of handling.

[0030] The fineness of the single fiber of the polyvinyl alcohol fiber of the present invention is not particularly limited, but is usually 1 to 1000 dtex, and finenesses of 2 to 1000 dtex and further 30 to 600 dtex can be widely used. The fiber length of the fiber may be appropriately set depending on the application of the fiber structure or the fiber containing a ferroelectric material described later. In addition, the tensile strength of the polyvinyl alcohol fiber of the present invention is preferably 0.1 cN / dtex or more, more preferably 0.5 cN / dtex or more.

[0031] The polyvinyl alcohol fiber of the present invention is produced by preparing a spinning dope containing the above-mentioned polyvinyl alcohol and the above-mentioned ferroelectric substance in a predetermined amount, and spinning the dope. The solvent of the spinning dope is water or an organic solvent. From the viewpoint of obtaining a fiber having high mechanical properties and dimensional stability, a substantially circular cross section, and a uniformity, the solvent of the spinning dope is preferably an organic solvent.

[0032] Examples of organic solvents include polar solvents such as dimethyl sulfoxide (hereinafter sometimes referred to as DMSO), dimethylacetamide, dimethylformamide, and N-methylpyrrolidone, polyhydric alcohols such as glycerin and ethylene glycol, and mixtures of these with rhodanide, lithium chloride, calcium chloride, zinc chloride, and other swelling metal salts, as well as mixtures of these solvents with each other or with water, etc. Among these, DMSO is the most preferable in terms of low-temperature solubility, low toxicity, low corrosivity, etc.

[0033] The concentration of polyvinyl alcohol in the spinning dope is appropriately selected depending on the composition, degree of polymerization, and solvent, but is generally in the range of 4 to 40% by mass. When the solvent of the spinning dope is an organic solvent, it is preferable to dissolve the dope under reduced pressure with stirring after nitrogen replacement in order to prevent oxidation, decomposition, crosslinking reactions, etc., and to suppress foaming. The liquid temperature of the spinning dope when discharged is preferably in the range of 50 to 150°C, within which the dope does not gel or decompose or become discolored.

[0034] The concentration of the ferroelectric substance in the spinning dope is appropriately set so that the amount of the ferroelectric substance in the obtained polyvinyl alcohol fiber falls within the above range.

[0035] The polyvinyl alcohol fiber of the present invention can be produced by spinning the spinning dope prepared as described above. The spinning method is not particularly limited, and examples thereof include a dry spinning method, a wet spinning method, and a dry-wet spinning method. Among them, the wet spinning method is preferable because of its high productivity, and the polyvinyl alcohol is discharged into a solidification liquid having a solidification ability. In particular, when the spinning dope is discharged from multiple holes, the wet spinning method is preferable to the dry-wet spinning method in terms of preventing the fibers from sticking together during discharge.

[0036] The wet spinning method is a method in which the spinning dope is discharged from a spinneret directly into a solidification bath, while the dry-wet spinning method is a method in which the spinning dope is discharged from a spinneret into air or an inert gas and then introduced into a solidification bath. Note that solidification in the present invention refers to the change of a fluid spinning dope into a non-fluid solid, and includes both gelation, in which the dope solidifies without changing its composition, and coagulation, in which the dope solidifies with a change in its composition.

[0037] When the solvent of the spinning dope is water, for example, a saturated aqueous solution of sodium sulfate can be used as the solidification liquid. When the solvent of the spinning dope is an organic solvent, for example, an alcohol such as methanol, ethanol, propanol, or butanol; a ketone such as acetone, methyl ethyl ketone, or methyl isobutyl ketone; a fatty acid ester such as methyl acetate or ethyl acetate; an aromatic compound such as benzene or toluene; or a mixture of two or more of these can be used as the solidification liquid.

[0038] In order to achieve sufficient solidification deep inside the fiber, it is preferable to use a solidification solvent mixed with the solvent of the spinning dope, and the mixed mass ratio of solidification solvent / dope solvent is preferably 95 / 5 to 40 / 60, more preferably 90 / 10 to 50 / 50, and most preferably 85 / 15 to 55 / 45. By mixing the dope solvent in the solidification bath, the solidification ability can be adjusted and the cost of separating and recovering the dope solvent and solidification solvent can be reduced.

[0039] Although there is no limitation on the temperature of the solidification bath, when the spinning dope solvent is an organic solvent, solidification is usually carried out at a solidification bath temperature between -15 and 30°C. From the viewpoint of uniform solidification and energy saving, the solidification bath temperature is preferably -10 to 20°C, more preferably -5 to 15°C, and particularly preferably 0 to 10°C. If the solidification bath temperature is outside this temperature range, the tensile strength of the obtained fiber may decrease. When the spinning dope is heated to a high temperature, it is preferable to cool the solidification bath in order to keep the solidification bath temperature low.

[0040] Next, the fibers removed from the solidification bath are wet stretched, for example. In the case of wet stretching, the stretching ratio is preferably 5 times or less from the viewpoint of the crystallinity of the resulting polyvinyl alcohol fiber, and is preferably 1 to 5 times, more preferably 1.2 to 3 times, from the viewpoint of mechanical properties and prevention of sticking. In order to suppress sticking of the threads, it is preferable to increase the wet stretching ratio within a range where no fuzz is generated. In order to increase the wet stretching ratio, it is preferable to perform wet stretching in two or more stages during the extraction process.

[0041] When the spinning dope solvent is an organic solvent, it is preferable to extract and remove the dope solvent from the filaments by contacting the filaments with an extraction bath mainly containing a solidification solvent. Wet stretching and extraction may be performed in the same process. This extraction process can shorten the residence time in the extraction bath by continuously flowing pure solidification solvent in a countercurrent direction to the running direction of the filaments. This extraction process can reduce the amount of spinning dope solvent contained in the filaments to 1% or less, especially 0.1% or less of the mass of the filaments, so this method is preferable. The contact time is preferably 5 seconds or more, especially 15 seconds or more.

[0042] In order to increase the extraction rate and improve the extraction, it is preferable to break up the filaments in the extraction bath. Prior to drying, it is also effective in preventing sticking by replacing the solvent of the spinning dope in the filaments with a solvent that has a high solidifying ability for polyvinyl alcohol, such as ketones such as acetone, methyl ethyl ketone, and methyl isobutyl ketone, applying a hydrophobic oil agent such as mineral oil, polyethylene oxide, silicone, or fluorine in the form of a solution or emulsion to the filaments, or shrinking the filaments before drying to relieve shrinkage stress during drying.

[0043] The fibers are then dried. From the viewpoint of the strength of the resulting polyvinyl alcohol fibers, the drying temperature is preferably 100° C. or higher, and more preferably 120° C. or higher. In order to further improve the mechanical properties of the fibers, dry heat drawing may be performed.

[0044] When the polyvinyl alcohol fiber of the present invention obtained as above is used as a fiber structure, it may be used in combination with other fibers. In the case of use in combination, the content of the polyvinyl alcohol fiber of the present invention in the fiber structure is preferably 40% by mass or more, more preferably 60% by mass or more, and particularly preferably 80 to 100% by mass, from the viewpoint of ease of decomposition in the natural environment. In addition, it may be used in combination with other materials such as metals and films made of other resins. Examples of the fiber structure include woven fabrics, knitted fabrics, cloth, nonwoven fabrics, and paper.

[0045] The polyvinyl alcohol fiber thus obtained is degreased and sintered to obtain a fiber made of a ferroelectric material in which the ferroelectric material is sintered and bonded. In the degreasing step, for example, the fiber is held at a maximum temperature of about 280°C for two hours to remove organic components. In the sintering step, for example, the fiber is held at a maximum temperature of about 1300°C for two hours to obtain a continuous fiber in which the ferroelectric material is sintered and bonded.

[0046] By degreasing and baking according to the above process, the polyvinyl alcohol is thermally decomposed, and the ferroelectric contained in the polyvinyl alcohol fiber is bonded to obtain a fiber made of a continuous ferroelectric. The baking temperature for this purpose is preferably 1200°C or higher. From the viewpoint of the electrical properties of the obtained fiber made of a ferroelectric, it is more preferable that the baking temperature is 1200°C or higher and 1400°C or lower.

[0047] For the degreasing and baking, an electric or combustion furnace is used, and more specifically, a continuous mesh belt furnace, a tubular furnace, etc. are mentioned.

[0048] From the viewpoint of ease of handling of the fiber made of the present ferroelectric, the fiber diameter of the fiber made of the present ferroelectric is preferably 100 μm or less, more preferably 90 μm or less, and more preferably 10 μm or more. The fiber diameter of the ferroelectric fiber can be adjusted to a predetermined diameter by controlling the fiber diameter of the polyvinyl alcohol fiber.

[0049] Fibers made of this ferroelectric material can be widely used as a dielectric material for ceramic multilayer capacitors, etc. Fibers made of this ferroelectric material can also be used as a modifier for polymers, rubbers, etc., and by adding them to polymer materials, composite materials with high dielectric constants can be obtained.

[0050] Fibers made of this ferroelectric material can be used in a wide variety of electronic materials, such as resins for fingerprint authentication sensors, resins for insulating materials for power generation, resins for antenna materials, various capacitor materials, capacitor materials for substrates with built-in passive elements, dielectric filters, vibration generators, conversion sensors, ignition devices, and memory. EXAMPLES

[0051] The present invention will be specifically described below with reference to examples, but the present invention is not limited to the following examples. The evaluation items and methods adopted in the following examples and comparative examples are as follows.

[0052] (1) Fiber preparation Polyvinyl alcohol fibers of each of the Examples and Comparative Examples were produced under the conditions described below.

[0053] (2) Handling test In the production of the polyvinyl alcohol fiber, the handleability was evaluated based on the following evaluation criteria. The thread has been wound on the bobbin for more than one hour without breaks; The thread has been wound on the bobbin without breaks for more than 30 minutes; good Thread breakage confirmed within 30 minutes: Not acceptable

[0054] (3) Measurement of relative dielectric constant Two pairs of electrodes were formed on the surface of the fiber in the longitudinal direction by sputtering to form circles with a diameter equivalent to 1 / 5 of the fiber diameter. Both electrodes were connected to a measurement probe, and the capacitance and IR were measured using an impedance analyzer. The relative dielectric constant was calculated from the measured values.

[0055] <Example 1> 100 parts by mass of polyvinyl alcohol with a degree of polymerization of 4000 and a degree of saponification of 99.8 mol% and 900 parts by mass of barium titanate were dissolved in DMSO at 90 ° C. for 5 hours with stirring to obtain a spinning solution with a polyvinyl alcohol concentration of 5% by mass. This spinning solution was spun through a nozzle with 80 holes and a hole diameter of 0.17 mmφ in a 5 ° C. methanol / DMSO = 80 / 20 solidification bath, and subjected to wet heat stretching of 1.2 times in a methanol bath at 20 ° C. Next, after extracting DMSO in the thread with methanol, a spinning oil was applied and dried at 120 ° C., and the obtained dried raw yarn was dry-heat stretched at 160 ° C. under the condition of a dry heat stretching ratio of 1.1 times (total stretching ratio TD = 1.3 times) to produce a barium titanate-containing polyvinyl alcohol fiber with a fiber diameter of 30 μm. The spinnability was good and the handling was excellent. The obtained polyvinyl alcohol fiber was placed in a tubular furnace and held at 280°C for 2 hours, and then held at 1300°C for another 2 hours. As a result, a ferroelectric fiber was obtained that maintained its fiber shape. The relative dielectric constant of this fiber was measured to be 2027, indicating that it had excellent electrical properties.

[0056] <Examples 2 to 5> In Example 1, the polymerization degree of the polyvinyl alcohol and the amount of the ferroelectric substance used were changed as shown in Table 1, and barium titanate-containing polyvinyl alcohol fibers were produced in the same manner as in Example 1. The results are shown in Table 1. In addition, the obtained polyvinyl alcohol fibers were fired in the same manner as in Example 1, and as a result, fibers made of a ferroelectric substance that maintained the fiber shape were obtained in all cases.

[0057] <Comparative Example 1> In Example 1, the degree of polymerization of the polyvinyl alcohol used was changed to 1700, and the amount of the ferroelectric was changed as shown in Table 1, and barium titanate-containing polyvinyl alcohol fibers were produced in the same manner as in Example 1. The results are shown in Table 1. Furthermore, when the obtained polyvinyl alcohol fibers were fired in the same manner as in Example 1, the fiber shape could not be maintained, and fibers made of a ferroelectric could not be obtained.

[0058] [Table 1]

[0059] From the above results, it can be seen that the polyvinyl alcohol fiber of the present invention is not cut during the spinning process even when the fiber diameter is as thin as 100 μm or less, and is easy to handle. Furthermore, the polyvinyl alcohol fiber of the present invention maintains its fiber shape even after sintering. The fiber made of the present ferroelectric material obtained in this way is easy to handle and can be used for various electronic materials.

Claims

1. A polyvinyl alcohol fiber comprising a ferroelectric material and polyvinyl alcohol having an average degree of polymerization of 2000 or more.

2. 2. The polyvinyl alcohol fiber according to claim 1, wherein the fiber diameter is 100 μm or less.

3. 3. The polyvinyl alcohol fiber according to claim 1, wherein the ferroelectric material is present in an amount of 20 to 1,900 parts by mass per 100 parts by mass of the polyvinyl alcohol.

4. 4. The polyvinyl alcohol fiber according to claim 1, wherein the ferroelectric has a relative dielectric constant of 300 or more.

5. The polyvinyl alcohol fiber according to any one of claims 1 to 4, wherein the ferroelectric material contains at least a metal titanate.

6. 6. The polyvinyl alcohol fiber according to claim 5, wherein the metal of the metal titanate is an alkali metal or an alkaline earth metal.

7. A fiber structure comprising at least a portion of the polyvinyl alcohol fiber according to claim 1 .

8. 7. The method for producing polyvinyl alcohol fiber according to claim 1, further comprising the steps of: adding a ferroelectric material and polyvinyl alcohol having a degree of polymerization of 2000 or more to an organic solvent to prepare a spinning dope; and discharging the spinning dope into a solidifying liquid having a solidifying ability for the polyvinyl alcohol polymer.

9. A method for producing a fiber made of a ferroelectric material, comprising calcining the polyvinyl alcohol fiber according to any one of claims 1 to 6 at 1200 to 1400°C.

Citation Information

Patent Citations

  • JP1973039724A

  • Production of fibrous ceramic

    JP1987289615A

  • Compound of high-strength zirconia based filament

    JP1989124624A

  • Manufacture of superconductive fiber of oxide

    JP1992192226A

  • Long fibrous alkali titanate and composite material containing the same

    JP1992202015A